Teaching primary art and design - Ogier, Susan (SAGE | Learning Matters, 2017)
Trainee and beginning teachers often find it hard to plan for and teach good art lessons as there is little guidance on subject knowledge and outstanding practice. This key text will provide primary trainee teachers with subject knowledge, expert advice and guidance along with practical solutions that are necessary to offer children the best possible experiences in art, craft and design, to ensure that they have access to a broad and balanced curriculum. Through guidance and support it will enable them to develop an understanding of the principles and values that underpin high standards and high expectations, and show good progress in the subject